2016
DOI: 10.1016/j.jct.2016.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Melting behaviour of americium-doped uranium dioxide

Abstract: a b s t r a c t (Uranium + americium) mixed oxides are considered as potential targets for americium transmutation in fast neutron reactors. Their thermophysical properties and notably their melting behaviour have not been assessed properly although required in order to evaluate the safety of these compounds under irradiation. In this study, we measured via laser heating, the melting points under inert atmosphere (Ar) of U 1Àx Am x O 2±d samples with x = 0.10, 0.15, 0.20. The obtained melting/solidification te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 51 publications
3
8
0
Order By: Relevance
“…This process has been observed by, e.g., D. Prieur et al in their study on Am/U oxide solid solution formation [12]. As discussed above, the resulting minor UO 2+x fraction is not detectable in the present work and might require a combination of spatially resolved and high (energy) resolution XAS techniques (i.e., U M-edge HERFD/PFY/HR-XANES, e.g., [66][67][68][69]) in future studies.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…This process has been observed by, e.g., D. Prieur et al in their study on Am/U oxide solid solution formation [12]. As discussed above, the resulting minor UO 2+x fraction is not detectable in the present work and might require a combination of spatially resolved and high (energy) resolution XAS techniques (i.e., U M-edge HERFD/PFY/HR-XANES, e.g., [66][67][68][69]) in future studies.…”
Section: Resultssupporting
confidence: 67%
“…Since recoil-induced Am-cation displacement in the UO2 lattice is not to be expected, the necessary charge balance might occur via formation of Am(III)O7 11− moieties with oxygen vacancies in the cubic, eight-fold coordinated cation site of the fluorite structure. Alternatively, UO2 can act as redox buffer: Am(IV) → Am(III) / UO2 → UO2 + x (3) This process has been observed by, e.g., D. Prieur et al in their study on Am/U oxide solid solution formation [12]. As discussed above, the resulting minor UO2+x fraction is not detectable in the present work and might require a combination of spatially resolved and high (energy) resolution XAS techniques (i.e., U M-edge HERFD/PFY/HR-XANES, e.g., [66][67][68][69]) in future studies.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The DFT+U approach was used with the help of Quantum Espresso v. In case of Am-doped UO 2 , the situation was found to be different. It was reported that americium introduced into the UO 2 lattice is predominantly in the Am(III) state [111][112][113][114][115][116][117][118]…”
Section: What We Can Know Defect Non-stoichiometry and Doping Effectsmentioning
confidence: 99%
“…In the field of nuclear fission research, there are several works dealing with the use of high power laser / material interactions for the investigation of the properties of fuel materials at high temperature, starting from the 80's [4,5]. Particularly, laser heating devices together with analysis diagnostics and temperature monitoring systems have been applied for the measurement of thermal properties (heat capacity, diffusivity, conductivity) [6] and thermodynamic properties (melting point, evaporation point, vapor pressure, equation of state) [7][8][9][10][11][12][13][14][15]. Combined laser heating with sample levitation and synchrotron x-rays has also allowed studying molten uranium dioxide structure at very high temperature (up to 3270K) [16].…”
Section: A Laser Heating Approachmentioning
confidence: 99%